2017
DOI: 10.1186/s41747-017-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal ultrasound tomography for breast imaging: a prospective study of clinical feasibility

Abstract: BackgroundTo describe the clinical set-up and evaluate the feasibility of multimodal ultrasound tomography (MUT) for breast imaging.MethodsThirty-two consecutive patients referred for breast imaging and 24 healthy volunteers underwent MUT. In the 32 patients, the examination discomfort was compared to that of mammography (n = 31), handheld ultrasound (HUS) (n = 27) and magnetic resonance imaging (MRI) (n = 4) on a scale from 1 (lowest discomfort) to 10 (highest discomfort). MUT investigation time was recorded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…[32] Using multimodal ultrasound tomography, which combines SoS with other biomarkers, such as acoustic attenuation, Forte et al did not observe statistically significant changes over the menstrual cycle. [33] Our results indicate that variations of breast density within the menstrual cycle, if at all present, are small (SoS variation 95% CI [−1.1,7.5] m/s equivalent to breast density variations between [−1.1,7.5]%). We found that there is no statistically significant difference in SoS and ΔSoS between the follicular and luteal phase among volunteers with very dense breasts.…”
Section: Discussionmentioning
confidence: 74%
“…[32] Using multimodal ultrasound tomography, which combines SoS with other biomarkers, such as acoustic attenuation, Forte et al did not observe statistically significant changes over the menstrual cycle. [33] Our results indicate that variations of breast density within the menstrual cycle, if at all present, are small (SoS variation 95% CI [−1.1,7.5] m/s equivalent to breast density variations between [−1.1,7.5]%). We found that there is no statistically significant difference in SoS and ΔSoS between the follicular and luteal phase among volunteers with very dense breasts.…”
Section: Discussionmentioning
confidence: 74%
“…Transmission-mode ultrasound-computed tomography (TUCT) can instead map the distribution of speed of sound and acoustic attenuation, which are representative of a different set of physiological tissue properties, such as stiffness, density, and temperature 20,21 . In this regard, TUCT has been used to map the distribution of speed of sound (SoS) and acoustic attenuation (AA) in the female breast 22,23 , where recent clinical trials suggest a superior performance with respect to standard screening approaches in terms of safety, examination time, and patient comfort 2426 .…”
Section: Introductionmentioning
confidence: 99%
“…with circular or rotating transducer setups, for a well-determined tomographic reconstruction. This leads to a complicated setup and acquisition workflow, hindering the clinical translation of USCT [16]- [19].…”
Section: Introductionmentioning
confidence: 99%